PENGEMBANGAN APLIKASI BERBASIS WEB UNTUK PERAWATAN MOBIL DAN PENGELOLAAN BENGKEL DENGAN METODE PROTOTIPE - Jondya, Aisha Gemala; Alva Davian Trisanto; Azizah Dinda Yukadifa; Muhammad Rizky Noval (Jurnal Sistem Informasi (JUSIN), 2025)
This study presents the development of CekMobilmu.com, a web-based application designed to support car owners and automotive workshop in Jakarta by facilitating the digital recording of vehicle maintenance and repair activities. In response to the increasing technological advancement and rising demand for efficient service documentation, the application provides features for logging service history, monitoring vehicle condition, and managing workshop operations. Employing the Prototype Method, the research was conducted through sequential stages of data collection, system design, implementation, and evaluation. Data were obtained using questionnaires, interviews, and comparative analysis with existing similar applications. The evaluation phase demonstrated that the application effectively assists users in tracking maintenance schedules and enables workshops to record and manage repair tasks more efficiently. CekMobilmu.com addresses the communication gap between vehicle owners and service providers, offering a centralized and practical solution for vehicle maintenance management.